CREDItoR: uma abordagem semiautomática para curadoria em repositórios educacionais digitais com foco em recursos educacionais abertos - Santos, Marcelo dos (2019)
The Universal Declaration of Human Rights ensures that every person has the right to access to education. In this direction, the democratization of access to information and open education, are constituted as mechanisms for the dissemination of educational content to society. In this context, open educational resources (OER) emerge, which are digital materials that encapsulate educational contents under licenses that guarantee the possibility of access, use, reuse and recombination of these materials. These OER are made available through digital educational repositories. The act of curing a content, that is, guaranteeing its quality is called curation. The Digital Curation is an expensive procedure in terms of time and human resources that ensures the preservation and accuracy of information. In this master's thesis, a semiautomatic approach is presented to assist the digital curation process, focusing on OER, in digital educational repositories inserted in institutional contexts, paying attention to the following indicators of Quality: Author's and teacher's reputation, reusability, alignment with the learning objectives and content quality. The CREDItoR approach is based on extracting such indicators from the perception of the teacher's expectation when proposing the use of OER in proposed activities to a group of students and the experience of these students when performing the activities with the OER provided by the teacher. In other words, the alignment between learning objectives and the use of the most appropriate OER is sought. The approach was evaluated through an experiment with the participation of 64 people involved with schooling at the medium and technical level, with 56 students and 8 teachers. The results indicated that combining the pedagogical expectation of the user to the experience of the use of the OER by the student provides the evaluation of the quality of these OER and can assist the process of digital curation when referring to educational repositories embedded in institutional contexts. The results indicated that combining the pedagogical expectation of the teacher to the experience of the use of the OER by the student provides the evaluation of the quality of these OER and can assist the process of digital curation when referring to digital educational repositories Inserted into institutional contexts.